PERNIKAHAN DI BAWAH UMUR PADA MASYARAKAT PESISIR MALANGKE - Salik, Yunus (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2020)
This article discusses early marriage in coastal communities. This study uses quality research. The phenomenon of underage marriage in North Luwu Regency is considered high in recent years. The reasons for early marriage occurring in North Luwu district are poverty and education which influence the occurrence of early marriage. Poverty is one of the causes of inability to access education and unemployment. Without education, there has been a paradigm shift and culture. Furthermore, the static paradigm is one of the reasons for the persistence of culture and customs, including culture and customs that are not prospective. The factors that cause the spouse to be underage because the prospective bride has become pregnant before marriage, is due to the weak economic condition of the community, due to the weak level of education of the community. This causes parents to prefer to marry off their children. The efforts taken by the Head of the Masamba Court, KUA, PPN Officers in minimizing the practice of underage marriage include PPN Officers also coordinating with PPN Assistant Officers who are scattered in each sub-district / village, coordination is carried out in relation to the VAT Assistance function which is the extension of VAT. PPN officers in minimizing the practice of underage marriage are by socializing the Marriage Law, especially regarding the age limit for a person to marry and the importance of registering marriage. The socialization process is carried out when giving wedding sermons and other religious events.